Effect of Dietary Pattern on the Emergence of Permanent Teeth of the Children of Larkana, Pakistan - Khan, Nazeer; Abbasi, Sarfraz Ali; Khan, Hasham; Baloch, Mujeeb ur Rehman; Chohan, Arham (Ibnosina Journal of Medicine and Biomedical Sciences, 2022)
Objective The aim of this study was to determine the association of eruption of permanent teeth of Sindhi children of Pakistan with the consumption of wheat, rice, meat, and milk.Methodology A team of two dentists (one male and one female) and two assistants (one male and one female) was trained and calibrated before the study and visited all the 26 selected schools on the prearranged time and date and all the children from kindergarten 1 to class 8 were screened. Children with at least one “just erupted” tooth were taken out of the class for further examination. Number of days of eating meat, rice, vegetable, and milk in a week along with date of birth and some other personnel information was recorded on a questionnaire sheet.Results One thousand two hundred five cases were collected from 26 schools, located in the city of Larkana and its suburbs. The minimum median value belonged to tooth number 16 and the maximum value was for tooth number 27. Twenty-two out of 28 teeth (79%) showed early eruption who consumed the meat more frequently than lesser time. Twenty-three out of 28 teeth (82%) showed early eruption for the children who consumed the vegetable diet a lesser number of times as compared with more frequent. Nineteen out of 28 teeth (68%) showed delayed eruption for those who consumed the rice a lesser number of times as compared with more frequent. Eighteen out of 28 teeth (64%) showed early eruption for the children who consumed a lesser amount of milk as compared with a greater amount.Conclusion The study concludes that a protein-rich diet accelerated, while calcium, mineral, and carbohydrate-rich food items delayed the eruption of permanent teeth among the children of Larkana.
Keywords: dieting patterns; just erupted tooth; Larkana (Sindh province); time of eruption